How cruelty-free logos influence Consumers’ Purchase Intention : the effects of Brand Image Logo Awareness and Moral Obligation - Cadete, Beatriz João Ramilo Gomes Pereira (2021)
In a world where consumers involve themselves in the causes they believe, ethical consumption is getting the public’s attention and cruelty-free products are no exception. According to the Humane Society International, the European Union is now the world’s largest cruelty-free cosmetic market. Despite that fact, in the literature, some space remains for investigation. This study intended to comprehend how purchase intention is influenced by the existence of cruelty-free logos on package and how it affects brand image. The moderation impact of logo awareness and moral obligation were also included in the analysis. To reach relevant conclusions, a focus group and a survey questionnaire were conducted. The last one was designed considering three different scenarios, which were randomly assigned to the respondents. Therefore, they could be confronted with a package without a cruelty-free logo, with an uncertified cruelty-free logo or with a certified cruelty-free logo. Overall, the results revealed that cruelty-free logos lead to higher purchase intentions and that the visual effect of the logo positively affects brand image. It was also proved that brand image mediates the relationship between the visual effect of the cruelty-free logo and purchase intention. The moderation effect of logo awareness and moral obligation were not confirmed.